2015
DOI: 10.1007/s13197-015-2140-5
|View full text |Cite
|
Sign up to set email alerts
|

Blends of rapeseed oil with black cumin and rice bran oils for increasing the oxidative stability

Abstract: For the increase of oxidative stability and phytonutrient contents of rapeseed oil 5, 10 and 20 % blends with rice bran oil and black cumin oil were prepared. Profiles of different bioactive lipid components of blends including tocopherols, tocotrienols, phytosterols and phytostanols as well as fatty acid composition were carried out using HPLC and GLC. Rancimat was used for detecting oxidative stability of the fatty material. The blends with black cumin seed oil characterized higher level of α- and γ-tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 25 publications
2
17
2
Order By: Relevance
“…The BS showed a remarkably high OSI value ( p < .05); therefore, addition of BS provided better oxidative stability to the SS oil ( p < .05) (Figure ). The higher oil stability could be explained by the improved antioxidant content of BS oil in the blends (Rudzińska et al, ). The results are in accordance with the data published by Kiralan et al () for the sunflower/black seed oil blend.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BS showed a remarkably high OSI value ( p < .05); therefore, addition of BS provided better oxidative stability to the SS oil ( p < .05) (Figure ). The higher oil stability could be explained by the improved antioxidant content of BS oil in the blends (Rudzińska et al, ). The results are in accordance with the data published by Kiralan et al () for the sunflower/black seed oil blend.…”
Section: Resultsmentioning
confidence: 99%
“…Among the edible oils, black cumin seed (BS) ( Nigella sativa ) oil is relatively stable and has many nutritional and health benefits (Khoddami, Ghazali, Yassoralipour, Ramakrishnan, & Ganjloo, ). BS oil contains high levels of bioactive compounds including phytosterols, high contents of total tocochromanols, β‐ and γ‐tocotrienol and γ‐tocopherol, and essential fatty acids (Rudzińska, Hassanein, Abdel‐Razek, Ratusz, & Siger, ).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the changes in the fatty acid composition of oils during heating is an effective method to examine thermal oxidation changes in the oils. The effects of thermal treatments on the oxidative degradation and physico-chemical properties of some vegetable oils as affected by added RBO have been reported elsewhere (Mishra and Sharma, 2014;Rudzińska et al, 2016;Sharma et al, 2006). Very few studies have reported on the oxidative changes and fatty acid composition of SO incorporated with RBO under adverse thermal conditions, and this is the main objective of the present study.…”
Section: Introductionmentioning
confidence: 85%
“…The major saturated fatty acids found in the samples were myristic, palmitic and stearic acids with the concentration of 0.29-0.42, 17.87-20.57 and 2.18-2.65 g/100 g oil, respectively. The four unsaturated fatty acids found were palmitoleic, oleic, linoleic and linole- 31,32 . The content of unsaturated fatty acids was higher than saturated fatty acids.…”
Section: Fatty Acid Pro Lementioning
confidence: 97%